Studies on the intertidal sandy-beach fauna of the Cape Peninsula - Brown, Alexander Claude (Department of Biological Sciences, 2015)
The thesis comprises six published papers and two papers in mnuscript. Five of the publications and the second of the manuscripts deal with the sandy-beach snail, Bullia, while the sixth published paper is a brief account of food-relationships on the Cape Peninsula's sandy beaches. The first manuscript is an introduction to the ecology of the sandy beaches of the Cape Peninsula, the first of a series of papers to be published on this topic. The manuscript on Bullia forms the second part of this series.